2016
DOI: 10.1002/art.39716
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: The Multi‐Biomarker Disease Activity Test for Rheumatoid Arthritis: Is It a Valid Measure of Disease Activity?

Abstract: One of the greatest unmet needs in rheumatology is a biomarker that enables highly sensitive and reliable measurement of disease activity in patients with rheumatoid arthritis (RA). Witness the enthusiasm of the rheumatology community for Vectra DA, the latest multibiomarker disease activity (MBDA) test, which was developed and marketed by Crescendo Biosciences and is available commercially in the US as a send-out laboratory test. This MBDA test measures 12 serum protein biomarkers using multiplex enzyme immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…In the absence of a clear understanding of which are the most relevant biomarkers to consider, we have looked at multiple types of biomarker analyses that could be useful in this endeavor; this included the MBDA test. We concur with the accompanying editorial published in the same issue of Arthritis & Rheumatology that encourages further efforts in this area (7), as there is a need to develop clinically relevant tools both for patients with RA and for clinicians. We look forward to the results of these efforts.…”
Section: Replysupporting
confidence: 68%
“…In the absence of a clear understanding of which are the most relevant biomarkers to consider, we have looked at multiple types of biomarker analyses that could be useful in this endeavor; this included the MBDA test. We concur with the accompanying editorial published in the same issue of Arthritis & Rheumatology that encourages further efforts in this area (7), as there is a need to develop clinically relevant tools both for patients with RA and for clinicians. We look forward to the results of these efforts.…”
Section: Replysupporting
confidence: 68%
“…Thresholds for DAS28-CRP RA disease activity categories are systematically lower than the corresponding cutoffs in the DAS28 using the erythrocyte sedimentation rate (ESR) (15,16), as noted in the editorial accompanying Fleischmann and colleagues' article (17). The comparison of MBDA scores versus DAS28-CRP in the article used the DAS28-ESR category thresholds, and therefore yielded more discordance than would have been expected between MBDA categories and DAS28-CRP categories using DAS28-CRP thresholds.…”
Section: To the Editormentioning
confidence: 99%
“…There was a modest correlation between MBDA, DAS28-CRP, and DAS28-ESR, with weaker correlations observed with SDAI, Clinical Disease Activity Index (CDAI), and Routine Assessment of Patient Index Data (RAPID3) [ 42 ]. However, subsequent post hoc analysis of data from the AMPLE trial (abatacept versus adalimumab for RA) showed disagreement between the MBDA test score and these measures [ 43 - 44 ]. One trial showed that the MBDA test may be useful in deciding whether or not to continue biologic therapy in the setting of clinical remission [ 45 ], and post hoc analyses of data have shown that a high baseline MBDA score is a strong independent predictor of radiographic progression at one year [ 46 - 49 ].…”
Section: Reviewmentioning
confidence: 99%